THU0015 Association of acid phosphatase locus 1*C ALLELE with the risk of cardiovascular events in rheumatoid arthritis patients. (23rd January 2014) - Teruel, M.; Martin, J.-E.; González-Juanatey, C.; Lόpez-Mejias, R.; Miranda-Filloy, J.A.; Blanco, R.; Balsa, A.; Pascual-Salcedo, D.; Rodriguez-Rodriguez, L.; Fernández-Gutierrez, B.; Ortiz, A.M.; González-Alvaro, I.; et al.
Abstract : Background: Acid phosphatase locus 1 ( ACP1 ) encodes a low molecular weight phosphotyrosine phosphatase implicated in different biological functions in the cell. Objectives: The aim of the present study was to determine the contribution of the ACP1 polymorphisms to the susceptibility to rheumatoid arthritis (RA) as well as the potential contribution of these polymorphisms to the increased risk of cardiovascular disease (CV) observed in RA patients. Methods: For this reason, a set of 1, 603 Spanish RA patient and 1, 877 healthy controls was included in the study. Information related to presence/absence of CV events was obtained in 1, 284 of them. All individuals were genotyped for four ACP1 single-nucleotide polymorphisms (SNPs), rs10167992, rs11553742, rs7576247, rs3828329, using a predesigned TaqMan SNP genotyping assays. Classical ACP1 alleles (*A, *B and *C) were imputed with SNP data. Results: No association of ACP1 gene polymorphisms with susceptibility to RA was observed. However, when RA patients were stratified according to the presence or absence of CV events an association of rs11553742*T with CV events was found ( P =0.012, OR =2.62 [1.24-5.53]). Likewise, ACP1*C allele showed evidence of association with CV events in patients with RA ( P =0.024, OR =2.43). Conclusions: Our data show that ACP1*C allele influences the risk of CV events in patients with RA. Acknowledgements: This work was supported by two grants from Fondo de Investigaciones Sanitarias PI06-0024 and PS09/00748 (Spain) and by RETICS Program, RD08/0075 (RIER) from Instituto de Salud Carlos III (ISCIII), within the VI PN de I+D+i 2008-2011 (FEDER). MT was supported by Spanish Ministry of Science through the program Juan de la Cierva (JCI-2010-08227). Disclosure of Interest: None Declared